Marginalization of Women Short story "INEM" by Pramodya Ananta Toer (Research on Feminism) - samsul samsul arifin; Sulistyaningsih Sulistyaningsih (JournEEL, 2023)
This article discusses the form of female exclusion in the short story Inem. By Pramoedya Ananta Toer. This article is a descriptive qualitative study. Data the source for this study is the short story "Inem" by Pramoedia Ananta Toer. The data for this study consisted of sentences, paragraphs, excerpts of conversations, and discourse describing forms of alienation. Data analysis techniques used this study is an essential technique. The research results are the exclusion of women affects not only society and culture,family, and even country. Finally, in a nutshell, the marginalization of women stories "Inem" Pramoedya Ananta Toer's work is not only born out of poverty and poverty. ignorant of his rights, but ignorant of the dominant role of patriarchal conventions and customs religious interpretation.